Zom-B clans - Shan, Darren (Shan, Darren. Zom-B (Series), 2014)
"While saving the town of New Kirkham, B's old friend, Vinyl, is kidnapped by the Ku Klux Klan. The Angels are prepared to do what it takes to save him, but B will have to make some very hard decisions about her loyalties"--